Relación entre la evolución sedimentaria de la laguna de Gallocanta (Cordillera Ibérica, NE de España) y la historia de la vegetación de su cuenca durante el Cuaternario reciente - Roc, A.C.; Sánchez Goñi, M.F.; Pérez, A.; Alfonso, S.; Jouanneau, J.M.; Sánchez, J.A. (Journal of Iberian Geology, 2002)
The analysis of the facies in the sediments from Gallocanta Lake allows the identification of three stages of sedimentation. The lowest stage related with the late Pleistocene corresponds with distal alluvial areas, the second stage reflects a shallow carbonated lake probably developed from the beginning of the Holocene to the Middle Age and, the last one corresponds to a saline-carbonated lake formed in the last centuries. In the alluvial facies the pollen concentration is very low. The following stages are related with different types of pollen assemblages. The stage of a shallow carbonated lake is associated with the development of a deciduous and evergreen Quercus forest in the basin and represents the maximum water depth, 4 to 10 meters, of the Gallocanta Lake. This period The last stage of saline-carbonated lake, dated at 1900 AD, coincides with the maximum phase of Olea cultivation contemporaneous with the decrease of the lake level. The depth of the water was between 0 and 2 m. The drying out of the Gallocanta lake coincides with the lake level lowering of other lakes in the Ebro basin suggesting a regional driving-factor (climatic and/or anthropic) as the main responsible for the observed desiccation of the last century.